Chapter Le Istituzioni della Rete URBE / The Istitutions of the URBE Network (Firenze University Press, 2025)
The profiles of the twenty higher education institutions that participate in the Roman Union of Ecclesiastical Libraries (URBE) are presented. For each institution, the history and disciplinary fields, the profile of the library and the main editorial activities are reported. Over 15 thousand students from over 100 countries of origin are enrolled. Parsifal embraces the richness of the library collections belonging to the URBE Network with the task of being a tool to facilitate access to knowledge by giving the same opportunity of visibility to all specializations and all original research languages.